g‐C3N4‐Based 2D/2D Composite Heterojunction Photocatalyst - Zhu, Bicheng; Cheng, Bei; Fan, Jiajie; Ho, Wingkei; Yu, Jiaguo (Small structures, 2021)
Employing semiconductor photocatalysis to transform solar energy into chemical energy provides a practicable strategy for the alleviation of energy and environmental crisis. Graphitic carbon nitride (g‐C3N4) is a popular 2D photocatalyst with numerous advantages, such as visible light response, low cost, and high stability. However, single g‐C3N4 photocatalyst displays poor performance due to fast recombination of photogenerated electrons and holes. To improve this limitation, many research works have focused on the construction of g‐C3N4‐based 2D/2D heterojunction photocatalysts by hybridizing g‐C3N4 with other 2D materials. The intimate face‐to‐face contact in 2D/2D heterojunction offers large contact area and plentiful channels for the migration and separation of photogenerated charge carriers. Furthermore, 2D/2D heterojunction inherits the strengths of 2D structure, including high specific surface area, abundant adsorption sites and active sites. Herein, the preparation, mechanism, and application of g‐C3N4‐based 2D/2D heterojunction photocatalysts are reviewed. Three common preparation methods are summarized, including solid phase reaction, in situ growth, and electrostatic self‐assembly. Various photocatalytic mechanisms are discussed, including traditional type‐II, Z‐scheme and S‐scheme mechanisms. A series of applications in energy and environment fields are illustrated. Finally, future directions for the development of g‐C3N4‐based 2D/2D heterojunction photocatalysts are proposed. g‐C3N4‐based 2D/2D composite heterojunction photocatalyst exhibits excellent photocatalytic performance because it inherits and integrates the advantages of 2D structure and heterojunction, such as efficient charge separation and abundant active sites. This review summarizes the preparation methods, photocatalytic mechanisms and applications of g‐C3N4‐based 2D/2D composite materials, and provides an outlook for the future development.